Human Resource Development Activities in a Retail Franchise in Thailand: The Case of Coffee World - Thanee Ngaochay (Journal of Economics and Behavioral Studies, 2015)
International franchising in a rapidly developing economy such as Thailand’s can offer a short cut to providing the newly-aspirant middle classes with the contemporary consumer goods brands they desire. The method also offers good opportunities for small scale investors and managers to obtain experience of managing high quality brands with full support from their international partners. However, they are likely to have to shoulder at least some of the burden of training their employees so that they are able to contribute to the overall service offering of the branch concerned. This paper uses a quantitative survey of 205 employees of the Coffee World franchise in Thailand to investigate the relationship between human resource development and organizational development in the businesses concerned. It is shown that the strengths of the relationships are limited and some ideas are provided for explaining why this might be.